Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 2 - Derivatives - 2.3 Differentiation Formulas - 2.3 Exercises - Page 140: 19



Work Step by Step

Make an «u» substitution in order to apply the chain rule and make it easier $G(u)=u^2$ $u=1+q^{-1}$ $u'=-q^{-2}$ Derivate $G'(u)=2u*u'$ Undo the substitution $G'(q)=2(1+q^{-1})(-q^{-2})$ $G'(q)=-2q^{-2}-q^{-3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.